Job Stress in Primary Care Nurses Facing the Covid-19 Pandemic - Acuña , Mercedes del Carmen; Castillo Benites , Ruth (SCT Proceedings in Interdisciplinary Insights and Innovations, 2025)
The new SARS-CoV-2 coronavirus or Coronavirus Disease 2019 (COVID-19) emerged in Wuhan, China and was officially declared as the source of the pandemic in March 2020 by the World Health Organization (WHO). Its impact on nursing was significant as it caused numerous stressors on staff working on the front line of care. The pandemic imposed new working conditions on nurses, which impacted on personal and work-related issues that were interrelated with the quality of health care. The present study aimed to determine the presence of Job Stress in primary care nursing professionals working in health centers belonging to the Route No. 18 corridor of Rosario during the first quarter of 2022. The study design was simple descriptive quali-quantitative and worked with only one variable: work stress. The instrument applied was a structured questionnaire called Occupational Stress Inventory which is divided into two parts: the first one that allowed us to obtain sociodemographic data and the second one that contains 3 sessions that allowed us to assess the physical and psychological signs and the internal factors of the work environment responsible for occupational stress with a total of 13 items, scored on a 3-point Likert-type scale that inquired about the frequency of occurrence of these using options with an answer range that vary from “1” never, “2” infrequent and “3” very frequent. This tool is an abbreviated adaptation of the Maslach MBI Inventory and was applied to 8 primary care nursing professionals working in health centers belonging to the Route No. 18 corridor of Rosario. The results were analyzed and interpreted in the Excel program and arranged in statistical tables, concluding that 50% of the ages of the nursing professionals surveyed ranged between 36 and 45 years, 25% between 25 and 35 and the remaining between 46 and 55 years. On the other hand, it was observed that 100% of the nursing professionals were female and that their academic level corresponded to the technical level. In addition, the study revealed that 62% of the professionals undertook training during the 2020/2021 period and, of the total, 50% had been working for between 1 and 5 years and only 13% had more than 11 years in the position. Coincidentally, 62% of the sample reported working the morning shift and having more than one job. With regard to the presence of physical signs of stress, 67% of the total number of nursing professionals surveyed responded that they were Very Frequently Stressed, while only 7.5% responded that they had never been stressed, but 47.5% had been Very Frequently Stressed. Likewise, the nursing professionals interviewed expressed that, in relation to the presence of internal factors of the work environment, these are present very frequently in 70% of them. As for the presence of work-related stress, 50% of the sample showed high levels, while 38% had medium levels of work-related stress.